The Influence of Influencers, Video Duration, and Discounts on Impulsive Buying of Bostanten Brand on TikTok Shop - Rika Andriani Br Sinaga; Mariyudi Mariyudi; Sapna Biby; Rahmaniar Rahmaniar (PT. Intelek Cendikiawan Nusantara, 2025)
This study aims to examine the influence of influencers, video duration, and discounts on impulsive buying behavior of Bostanten products in TikTok Shop. The research was conducted using a quantitative approach with primary data collected through questionnaires distributed to 100 respondents who had previously purchased Bostanten products. Multiple linear regression analysis with SPSS version 25.0 was employed to test the proposed hypotheses. The findings indicate that influencers have a positive and significant effect on impulsive buying (p-value 0.002 < 0.05; t-value 1.756 > t-table 1.665). Video duration also shows a significant and positive impact (p-value 0.004 < 0.05; t-value 2.943 > t-table 1.665). Similarly, discounts significantly influence impulsive buying (p-value 0.001 < 0.05; t-value 3.327 > t-table 1.665). The adjusted R² value of 0.583 demonstrates that 58.3% of impulsive buying behavior can be explained by the independent variables, while the remaining 41.7% is influenced by other factors not included in this model. These results highlight the importance of social media marketing strategies, especially the role of influencers, engaging video content, and price promotions, in shaping consumer impulsive buying decisions. The study contributes to the understanding of digital marketing effectiveness and provides insights for practitioners in designing promotional strategies on social commerce platforms such as TikTok Shop.